Process technology for distortion compensation by means of gas quenching in flexible jet fields. (7th October 2005) - Schuettenberg, S.; Frerichs, F.; Hunkel, M.; Fritsching, U.
Controlled inhomogeneous quenching (hardening) of a work-piece within the heat treatment process opens up the possibility of compensation of distortion potential. Suitable heat transfer conditions of the workpiece within the quenching process are realised by impressing and regulation of adjusted (spatially and/or time-wise varying) flexible flow fields on the basis of gas jet arrays. For analysis of work-piece distortion in heat treatment, the local asymmetric quenching process in gaseous media is analysed and described, modelwise, within the framework of the Collaborative Research Centre (SFB570) 'Distortion Engineering' at the University of Bremen. Here, the potential of measures for avoidance as well as reduction of distortion within the manufacturing process is appraised on the basis of simulation and experimental models. The aim of the examinations in the present project is the appliance of in-line control of asymmetric quenching conditions as compensative measures in the flexible gas quenching process. In this contribution, the process technology for distortion compensation in asymmetric flow fields is introduced.